Comparison of a mixed modes solar dryer to a direct mode solar dryer for African indigenous vegetable and chili processing. Issue 6 (9th January 2017) - Ayua, Emmanuel; Mugalavai, Violet; Simon, James; Weller, Stephen; Obura, Pamela; Nyabinda, Naman
Abstract: A mixed modes solar dryer was modified from a Horticultural Innovation Laboratory design and its performance compared to a direct mode solar dryer to process horticultural crops. The mixed modes and the direct mode solar dryers dried vegetables at different rates with the mixed modes being faster for all products ( p ≤ .001). Leaves and flowers of the spider plant ( Cleome gynandra ) had the shortest drying time (270 ± 6 min) while the fruit of the African bird's eye chili ( Capsicum frutescens ) took the longest time (3, 866 ± 31 min). Moisture content of the dried vegetables met the industry standard for dehydrated fruits and vegetables (≤8.4%) and of chilies which had a moisture content of (9.5 ± 0.15%). This low cost mixed modes dryer is suitable for small‐scale vegetable processors and farmers as it does not require grid electricity to operate. Practical applications: Fruits and vegetable production is a key economic activity in Kenya. To preserve such produce, farmers practice open sun drying which not only takes longer to dry produce than solar dryers but is also prone to contamination from flies and dust. Prolonged drying times result in products with inconsistent colors and lower nutritional value. Yet, there are simple low cost mixed modes dryers that can be used to dry fruits and vegetables faster than open‐air solar drying. The study aimed at providing local farmers with a modified mixed modes solar dryer to quickly dry fresh produce with a minimal loss of nutrients and color retention in the final product. Globally, such a dryer can be used as one of the simplest innovations toward reduction of postharvest food losses of fruits and vegetables.